2017
DOI: 10.1089/brain.2016.0458
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Network Differences in Master Sommeliers: Connectivity Analysis Using Granger Causality and Graph Theoretical Approach

Abstract: Previous studies investigating the differences in olfactory processing and judgments between trained sommeliers and controls have shown increased activations in brain regions involving higher level cognitive processes in sommeliers. However, there is little information about the influence of expertise on causal connectivity and topological properties of the connectivity networks between these regions. Therefore, the current study focuses on addressing these questions in a functional magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…We found that the connectivity originating in those three areas (corresponding with visual cortex, somatomotor area, and frontal area) was stronger in media professionals. This is coincident with previous studies that attributed stronger connectivity in professionals compared with control groups to the learning undertaken because of their expertise (Sreenivasan et al, 2017 ), and that suggested an increased neural efficiency in the brain of highly skilled individuals (Bernardi et al, 2013 ). The fact that that higher connectivity in media professionals occurs in visual cortex could be related to the importance of that area for visual processing in their daily work.…”
Section: Discussionsupporting
confidence: 91%
“…We found that the connectivity originating in those three areas (corresponding with visual cortex, somatomotor area, and frontal area) was stronger in media professionals. This is coincident with previous studies that attributed stronger connectivity in professionals compared with control groups to the learning undertaken because of their expertise (Sreenivasan et al, 2017 ), and that suggested an increased neural efficiency in the brain of highly skilled individuals (Bernardi et al, 2013 ). The fact that that higher connectivity in media professionals occurs in visual cortex could be related to the importance of that area for visual processing in their daily work.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, studies (Kawabata and Zeki, 2004 ; Vartanian and Goel, 2004 ) have shown that expertise influences aesthetic judgments, and architects with aesthetic expertise (Kirk et al, 2009 ) showed differential activation of the bilateral subcallosal cingulate gyrus and medial orbitofrontal cortex compared to non-architects during this judgment. Furthermore, sommeliers (wine experts) (Pazart et al, 2014 ) also showed activation in the temporal pole and hippocampal and parahippocampal formations when tasting wine; Sreenivasan et al ( 2017 ) have explored the influence of expertise on causal connectivity and topological property related to master sommeliers during different olfactory and non-olfactory tasks, where in sommeliers, a significantly greater connectivity involving the precuneus, caudate, putamen, and several frontal and temporal regions was observed and a significantly higher small-world topology was identified.…”
Section: Occupational Neuroplasticitymentioning
confidence: 99%
“…Previous studies have used task-related and resting functional magnetic resonance imaging (fMRI) to examine olfactory networks, using primary olfactory and orbitofrontal cortices as seed regions (Banks et al, 2016; Cecchetto et al, 2019; Fjaeldstad et al, 2017; Karunanayaka et al, 2017; Karunanayaka et al, 2014; Kiparizoska and Ikuta, 2017; Kollndorfer et al, 2015; Krusemark and Li, 2012; Nigri et al, 2013; Sreenivasan et al, 2017; Sunwoo et al, 2015). These studies have contributed important broad knowledge of parallel olfactory networks (Karunanayaka et al, 2014), how they compare to trigeminal networks (Karunanayaka et al, 2017), and how they change with age (Wang et al, 2005) and disease (Caffo et al, 2010; Fjaeldstad et al, 2017; Killgore et al, 2013; Sunwoo et al, 2015; Wang et al, 2010; Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%